Prabowo and the shifts in Indonesia’s contemporary foreign policy: unboxing a leader’s Operational Code - Bama Andika Putra (Cogent Social Sciences)
Since being inaugurated as the eighth president of Indonesia, Prabowo has attracted some concerns about the trajectory of Indonesia’s foreign policy under his rule. In November 2024, Indonesia and China concluded a Joint Statement that would potentially abandon Indonesia’s decade-long held foreign policy in the South China Sea. Equally puzzling is Indonesia’s membership in the emerging power bloc, BRICS (Brazil, Russia, India, China, and South Africa) in early 2025. How can we make sense of these empirical anomalies? Bridging the foreign policy analysis literature of the ‘Operational Code Approach’, this empirical explanatory case study looks at Prabowo’s foreign policy in 2024 and 2025. It provides a socio-psychological analysis of the leaders’ operational code. Doing so considers the relevance of Prabowo’s ‘philosophical’ and ‘instrumental’ beliefs in shaping Indonesia’s contemporary policies. As a result, this study considers the relevance of Prabowo’s personal beliefs as influencing a subjective interpretation of Indonesia’s foreign policy doctrine of a free and active foreign policy, influenced by Prabowo’s anti-oppression norms, fear of colonialism, military background, and appetite to secure economic interests.